Applications of Biodegradable Magnesium-Based Materials in Reconstructive Oral and Maxillofacial Surgery: A Review - Sanja Vujović; Jana Desnica; Dragana Stanišić; Irena Ognjanović; Momir Stevanovic; Gvozden Rosic (Molecules, 2022)
Reconstruction of defects in the maxillofacial region following traumatic injuries, craniofacial deformities, defects from tumor removal, or infections in the maxillofacial area represents a major challenge for surgeons. Various materials have been studied for the reconstruction of defects in the maxillofacial area. Biodegradable metals have been widely researched due to their excellent biological properties. Magnesium (Mg) and Mg-based materials have been extensively studied for tissue regeneration procedures due to biodegradability, mechanical characteristics, osteogenic capacity, biocompatibility, and antibacterial properties. The aim of this review was to analyze and discuss the applications of Mg and Mg-based materials in reconstructive oral and maxillofacial surgery in the fields of guided bone regeneration, dental implantology, fixation of facial bone fractures and soft tissue regeneration.